An experimental and numerical investigation of the role of rivet and die design on the self-piercing riveting joint characteristics of aluminum and steel sheets. (September 2021) - Karathanasopoulos, N.; Pandya, Kedar S.; Mohr, D.
Abstract: We analyze the role of different rivet and die design parameters on the feasibility and quality of the self-piercing riveting (SPR) joining of metallic sheet stacks. In particular, the riveting of a similar aluminum-to‑aluminum sheet stack (AA2019/AA7075-F) and a dissimilar aluminum-to-steel sheet stack (AA7075-F/BA0270) is investigated, both experimentally and numerically. Towards this, the different rivet and sheet materials are experimentally characterized to obtain their elastoplastic and fracture attributes. Thereafter, SPR process finite element models are developed. Initially, the joint feasibility is experimentally probed for specific available rivet and die configurations, thus identifying SPR process parameters that allow for successful joining. Thereafter, a wider range of SPR process parameters is investigated numerically. It is observed that a combination of successful joint formation and high interlock values is obtained over specific ranges of rivet leg thickness and die depth values. Moreover, low rivet leg thickness values and near-unity normalized die depths – with the sum of the die depth and total sheet thickness normalized with respect to the rivet leg length – yield high quality SPR joints for both types of stacks considered. However, the optimum parameter selection is stack-specific, with high-quality AA2019/AA7075-F SPR joints observed to be feasible over a more constrained parametric space compared to the AA7075-F/BA0270 joining case. Further, it is concluded that the mean von Mises stress induced in the sheets after the SPR process is primarily affected by the selection of the die depth, with the induced stress being less sensitive to other design parameters, such as the rivet leg thickness or die shape for both joining cases. Graphical abstract: Unlabelled Image Highlights: The joining of Al-Al (AA2019/AA7075-F) and Al-Steel (AA7075-F/BA0270) sheets is experimentally and numerically investigated. Rivet and die material and geometric parameters allowing for successful joining are identified. Combinations of rivet leg thickness and die depth values that favor high interlock joints are provided. The effect of the rivet and die design on the induced Von Mises stresses is analyzed.